2016
DOI: 10.1017/s1478951516000869
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life experiences and deathbed phenomena as reported by Brazilian healthcare professionals in different healthcare settings

Abstract: Our study revealed that ELE reports are not uncommon in clinical practice and seem to be little influenced by religious or spiritual beliefs. Although strongly reported in all settings, palliative care professionals tend to be more open to this issue and have a stronger perception of ELEs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
10
35
0
Order By: Relevance
“…In Fenwick et al.’s (2010) five-year retrospective study of end-of-life experiences, 62% and 64% of the participants had deathbed phenomena related to them by patients or by patients’ relatives, respectively. Thirty-four percent of the hospice palliative care volunteers surveyed by Claxton-Oldfield and Dunnett (2016) had personally witnessed a patient having a DBV, and 48% had a patient or patient’s family member tell them about their dying loved one “seeing” a relative or friend who had long since died, and in a multicentre study in Brazil, 70% of the health-care professionals interviewed reported observing EOLP or being told about them (Dos Santos et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In Fenwick et al.’s (2010) five-year retrospective study of end-of-life experiences, 62% and 64% of the participants had deathbed phenomena related to them by patients or by patients’ relatives, respectively. Thirty-four percent of the hospice palliative care volunteers surveyed by Claxton-Oldfield and Dunnett (2016) had personally witnessed a patient having a DBV, and 48% had a patient or patient’s family member tell them about their dying loved one “seeing” a relative or friend who had long since died, and in a multicentre study in Brazil, 70% of the health-care professionals interviewed reported observing EOLP or being told about them (Dos Santos et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Although a cultural and/or religious influence has been suggested, 10,21 there are many similarities between scientific reports from several different cultures/countries. 12,14,16,18,20,22 The prevalence of ELEs varies among studies between 20% and 90%, 7,16,18 with higher percentages reported by studies in which patients were asked about their experiences directly. 18,19 Despite the fact that ELEs are not uncommon, many clinicians are unaware or neglectful of the phenomenon due to the risk of being considered unprofessional.…”
Section: Introductionmentioning
confidence: 99%
“…Depner, et al; Palliative Medicine Reports 2020, 1.1 http://online.liebertpub.com/doi/10.1089/pmr.2020.0037 exemplified this, saying ''it was comforting to see the trees and it was a beautiful fall day, I felt happy.'' Equally, this category included emotions typically viewed as distressing: (1) uncertain/confused/ puzzled, (2) disturbing/distressing/scary/fearful/upset, (3) mad/angry/frustrated/disappointed/irritated, (4) worried/anxious/stressed/overwhelmed/concerned, (5) surprised/startled/shocked, and (6) sadness/sorrow/ blue. One participant reported a specific affective experience, ''I was watching children play in my house and someone got hurt I was very upset by this.…”
Section: Cqr Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The ELDVs involve mental and sensory activity while the patient is asleep (dreams) or awake (visions) and are typically reported to include seeing or feeling the presence of deceased loved ones. Research has evolved from case-based anecdotes and caregiver secondhand accounts 4,5,9,11,[13][14][15][16][17] to reports of patient perspec-tives. 1,2,10 More recently, the scope of ELDV research has expanded to explore the impact on post-traumatic growth of patients 6 and bereavement outcomes of familial caregivers.…”
Section: Introductionmentioning
confidence: 99%